Imaging classification and surgical strategy of retroperitoneal vascular leiomyosarcoma: experience from a single medical center - Bin Yang; Xun Zhao; Guoliang Wang; Hongxian Zhang; Lulin Ma; Lei Liu; Shudong Zhang (BMC Cancer)
Abstract Background Retroperitoneal vascular leiomyosarcoma (RVLMS), which originates from vascular wall smooth muscle cells, typically requires inferior vena cava (IVC) reconstruction during radical surgery. Methods A retrospective cohort study was conducted on 24 patients who underwent primary resection of RVLMS from June 2015 to November 2023 in one institution. The patient details, operative management, and follow-up data were assessed. Results Regarding the imaging classification of RVLMS, 6 patients were intraluminal type, 9 patients were intermediate type, 4 patients were extraluminal type, and 5 patients were peripheral type. The median tumor size was 80 mm (interquartile range, IQR 63–105 mm). The median operative time was 294 min. The median blood loss was 650 ml. There were significant differences in operation time, blood loss, blood transfusion, and Intensive Care Unit admission rate among the four types of RVLMS. The procedures of vascular reconstruction included primary repair (n = 15), patch angioplasty (n = 2), and IVC ligation (n = 4). 3 patients suffered an R1/R2 margin. With a median follow-up time of 12.5 months, 5 patients developed local recurrence while 7 patients developed distant metastasis. 1 patient had both local recurrence and distant metastasis. The median disease-free survival was 19.0 months (IQR 7.0–59.0 months). Conclusion A reasonable surgical strategy of vascular resection and reconstruction in the context of RVLMS surgery was of value in achieving good postoperative outcomes and long-term survival. The imaging classification of RVLMS might help to evaluate the surgical complexity and the prognosis.